Análisis de la sequía y desertificación mediante índices de aridez y estimación de la brecha hídrica en Baja California Sur, noroeste de México - Enrique Troyo Diéguez; Gustavo Mercado Mancera; Arturo Cruz Falcón; Alejandra Nieto Garibay; Ricardo D. Valdez Cepeda; José Luis García Hernández; Bernardo Murillo Amador (Investigaciones Geográficas, 2014)
In Baja California Sur ( BCS ), Mexico, dry-semi warm and warm climates prevail associated to an extreme trend of diurnal temperatures and the environmental dry-ness. In this State, the maximum summer t exceeds 40° C and the minimum varies from 5 to 12° C, with a minimal for the State of 2° C in winter, at the top of the Sierra de La Laguna; only Los Cabos region has a warm humid climate. Because precipitation in the state is low, oscillating from 310 mm in the southern area of the state to 120 mm per year in the northern portion, predictions and scenarios under climate conditions point to an intensification of droughts. The aim of this work was to carry out a comparative analysis of trends of temperature, precipitation and hydro-environmental aridity among contrasting localities of BCS, by means of the application of Aridity Indexes and the determination of the Standardized Water Gap (BHE), through a numerical scale modification of the De Martonne Index. With the values of temperature and precipitation for the different climate change scenarios for four weather stations, the indicators Hydro Environmental Availability Index (IDHA) and Hydro Environmental Drought Index (ISHA) were calculated to determine their trend and the consequent BHE , an innovative quantification of water deficit, which is proposed in this paper. The maximum value of BHE (10 units), indicating prevalence of drought, is observed from February to June in almost the entire state. Results suggest that BHE tend to increase and intensify under climate change conditions, which is more evident from the South towards the North of the State. According to the trends of the indexes IDHA, ISHA and BHE, under six scenarios of climatic change for four regions of BCS , BHE can be estimated with a major significance for the region Gustavo Díaz Ordaz-Vizcaíno, Mulegé County, in the North of the State, where may reach a value BHE max = 10 and BHE min = 7.23, values which suggest extreme dryness, corresponding to the maximum values among localities. We conclude that the analysis of trends in PP and t and their integration into bi-parametric indicators are a reliable tool for the construction of scenarios and climate change trends.